Demanda ocupacional de la Carrera Administración Pública de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López período 2015-2016. - Núñez Cuabú, Lucy Daniela (2018)
The purpose of the research was to follow-up graduates on the occupational demand and on-going training of the graduates of the Public Administration career at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. Research techniques were applied, in this way it was possible to know the deficiencies that occur in the professionals training and actions were taken that help to improve and update the curricular mesh according to the current requirements of the Engineers in Public Administration. In addition, the survey and the interview, reflected that the employability of the graduates is a difficulty once they finish their university studies, because the institutions demand professionals with work experience, this being a great limitation requirement. Based on the inquiry, a report was made, which emphasizes a structured outline of the aspects that should be included in the study plan, with the purpose that future professionals have a high level of knowledge that allows them to be competitive in the labor market and with this the existing unemployment rate decreases.